Vortex flows in acid solutions of lithium dihydrogen phosphate in a crystal growth unit - Iurchenko, A.N.; Kulik, K.N.; Voronov, A.P.; Babenko, G.N. (Functional Materials, 2015)
The characteristic properties of vortex flow induced by an external source under certain boundary conditions are established. Experimentally obtained are the data on the vortex size depending on the power of the source. The analytically established dependence is in agreement with the experimental data.